Religion and Business: Capitalization of Religion in Online Ta'aruf Accounts - Hidayat, Akhmad Alfian; Arifin, Ahmad Zainal; Falah, Mohammad Bachrul (Transformatif, 2024)
Research on the capitalization of religion in online ta